Improving Students’ Reading Skill on Descriptive Text by Using Picture Word - Yiwa, Rusmiyati Florensa; Yahmun, Yahmun (UIBU, 2024)
This study aims to improve students' reading skills in descriptive texts through the use of picture word media at SMP Negeri 1 Umalulu in the 2023/2024 academic year. The study subjects consisted of 50 students in grade VIII-A, including 25 boys and 25 girls. The research method used was Classroom Action Research (CAR) with a mixed approach (qualitative and quantitative). Data were collected through interviews, reading tests, observations, and questionnaires. The study was conducted in two cycles. In the first cycle, activities included a pre-test and post-test I, which focused on learning descriptive texts. In the second cycle, learning continued with more intensive use of picture word media, and concluded with a post-test II. The results showed a significant improvement in students' reading skills. The average pre-test score of 44.6 increased to 64.6 in the post-test I in the first cycle. In the second cycle, the average score increased further to 80. Furthermore, in the first post-test, 26 students (52%) achieved a score of 70 or higher, while in the second post-test, this number increased to 42 students (84%). These findings indicate that the use of picture words is effective in improving descriptive text reading skills. Furthermore, student enthusiasm and engagement in the learning process also increased, as reflected in the observation results, which showed a high score (4), indicating the creation of an active and conducive learning environment.